2023
DOI: 10.1097/md.0000000000033301
|View full text |Cite
|
Sign up to set email alerts
|

Association between thyroid dysfunction and venous thromboembolism: A systematic review and meta-analysis

Abstract: Background: Thyroid dysfunction plays an important role in the development of cardiovascular disease. However, its relationship with venous thromboembolism (VTE) remains unclear. We performed a meta-analysis of published cohort and case-control studies to investigate the association between thyroid dysfunction and VTE comprehensively. Methods: Three reviewers independently searched EMbase, PubMed, China national knowledge infrastructure, and Cochrane Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…A large population study of 53,418 patients registers that in patients with hyperthyroidism, the risk of pulmonary embolism is 2.31 times higher than the control group during a 5-year follow-up after adjusting for confounding factors [ 40 ]. A meta-analysis that included 15 studies up until October 2022 found an increased risk of venous thromboembolism (VTE) even in patients with subclinical hyperthyroidism (OR 1.33, 95% CI: 1.29–1.38) [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A large population study of 53,418 patients registers that in patients with hyperthyroidism, the risk of pulmonary embolism is 2.31 times higher than the control group during a 5-year follow-up after adjusting for confounding factors [ 40 ]. A meta-analysis that included 15 studies up until October 2022 found an increased risk of venous thromboembolism (VTE) even in patients with subclinical hyperthyroidism (OR 1.33, 95% CI: 1.29–1.38) [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…The significance of the data on hyperthyroidism as a probable prothrombotic condition has not been sufficiently implemented in clinical practice, nor are large studies consistent in asserting the association between elevated thyroid hormone values and thrombotic events [ 1 , 2 ]. The results of a new meta-analysis and the findings of other authors indicate that the prothrombotic milieu induced by hyperthyroidism contributes to the increased risk of venous thromboembolism (OR 1.322, 95% CI: 1.278–1.368) [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Several NCDs, but not all, included in the multimorbidity study by Barnett et al 14 have been associated with VTE. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] For some associations between NCDs and VTE, the associations are bidirectional, [36][37][38] for example, atherosclerotic disease and atrial fibrillation, but for most NCDs, the association with VTE is unidirectional. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] However, to the best of our knowledge, the association between multimorbidity and its severity (ie, number of NCDs) and VTE has not been studied.…”
Section: Open Accessmentioning
confidence: 99%